2014
DOI: 10.1542/peds.2014-1209
|View full text |Cite
|
Sign up to set email alerts
|

Feedback on Oral Presentations During Pediatric Clerkships: A Randomized Controlled Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Delivering competent oral case presentations is an important clinical communication skill, yet effective means of improving trainees' presentations have not been identified. WHAT THIS STUDY ADDS:Oral presentation feedback sessions facilitated by faculty by using an 18-item competency-based evaluation form early in pediatric clerkships improved medical students' subsequent oral presentations. Medical schools should consider implementing this evidence-supported practice. abstract OB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…There were 1974 participants, including 660/1463 (45%) men from 13 studies that reported gender data 33 38 42–52. Included studies involved students (medical, mixed health professions and pharmacy) (1869, 95%) in 16 studies,33 37 38 42–45 47–55 and doctors (105, 5%) in four studies 31 39 46 56. All studies included assessment of a discrete task except two studies that involved longitudinal evaluations 39 46.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 1974 participants, including 660/1463 (45%) men from 13 studies that reported gender data 33 38 42–52. Included studies involved students (medical, mixed health professions and pharmacy) (1869, 95%) in 16 studies,33 37 38 42–45 47–55 and doctors (105, 5%) in four studies 31 39 46 56. All studies included assessment of a discrete task except two studies that involved longitudinal evaluations 39 46.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included assessment of a discrete task except two studies that involved longitudinal evaluations 39 46. Three studies evaluated performance in a clinical practice setting (involving teaching skills,39 professional and communication skills46 and oral case presentations),55 and the remaining 17 assessed performance in a simulated environment (surgical procedures, nasogastric tube insertion, intubation, hearing test, pharmacy consultation or CPR)31 33 37 38 42–45 47–54 56 (see ‘Included studies’ section in the supplementary material for more details, online supplementary appendix 3).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, trainees may begin to devalue external feedback in general, relying instead on self-assessment [ 10 , 11 ]. It is encouraging that this need not be the case, and the quality of feedback improves after specific training of clinical faculty [ 29 , 54 , 55 ].…”
Section: Background Evidence To Guidelines For the Individual Clinicamentioning
confidence: 99%
“…O ral case presentation (OCP) is recognized as a central educational and patient care activity in a variety of clinical settings. Interestingly, most of the scholarly focus on OCP has occurred in internal medicine [1][2][3][4][5] and pediatrics; 6,7 in other areas, OCP is paid little attention. The emergency medicine OCP (EM-OCP) represents a particularly salient example of this problem due to the chaotic and fast-paced clinical environment.…”
mentioning
confidence: 99%
“…1,4 Two pediatric randomized controlled trial (RCTs) have evaluated the effect of detailed feedback and of an online module on students' OCP delivery. 6,7 Although many aspects of the OCP are transferable among specialties, the nature of EM demands a modified version. The EM-OCP dictates whether emergent or urgent action is needed, assesses for life-threatening conditions, and determines the allotment of finite resources in a busy department.…”
mentioning
confidence: 99%